Reading-Induced Shifts in Speech Perception in Dyslexic and Typically Reading Children - Romanovska, Linda; Janssen, Roef; Bonte, Milene (Frontiers in Psychology, 2019)
One of the proposed mechanisms underlying reading difficulties observed in developmental dyslexia is impaired mapping of visual to auditory speech representations. We investigate these mappings in 8-10 year-old typically reading and dyslexic children using text-based recalibration. In this paradigm, an ambiguous speech sound between /aba/ and /ada/ is combined with disambiguating text to shift the perception of the speech sound toward the text in subsequent auditory-only post-test trials. Research in adults shows this shift in the perception of ambiguous speech in typical, but not in dyslexic readers. Our results instead show significant text-induced recalibration in both dyslexic and typically reading children. Furthermore, the strength of the effect was predicted by the child’s individual phoneme categorization curve, suggesting a close link between phoneme perception and short-term text-induced audiovisual learning across both groups. Finally, phoneme categorization and recalibration strength were associated with reading skills in typically reading but not in dyslexic children. Taken together, our study highlights the importance of considering dynamic developmental changes in reading, letter-speech sound coupling and speech perception when investigating group differences between typical and dyslexic readers.